Pre and post synaptic NMDA effects targeting Purkinje cells in the mouse cerebellar cortex. - Etienne Lonchamp (Public Library of Science (PLoS), 2012)
N-methyl-D-aspartate (NMDA) receptors are associated with many forms of synaptic plasticity. Their expression level and subunit composition undergo developmental changes in several brain regions. In the mouse cerebellum, beside a developmental switch between NR2B and NR2A/C subunits in granule cells, functional postsynaptic NMDA receptors are seen in Purkinje cells of neonate and adult but not juvenile rat and mice. A presynaptic effect of NMDA on GABA release by cerebellar interneurons was identified recently. Nevertheless whereas NMDA receptor subunits are detected on parallel fiber terminals, a presynaptic effect of NMDA on spontaneous release of glutamate has not been demonstrated. Using mouse cerebellar cultures and patch-clamp recordings we show that NMDA facilitates glutamate release onto Purkinje cells in young cultures via a presynaptic mechanism, whereas NMDA activates extrasynaptic receptors in Purkinje cells recorded in old cultures. The presynaptic effect of NMDA on glutamate release is also observed in Purkinje cells recorded in acute slices prepared from juvenile but not from adult mice and requires a specific protocol of NMDA application.